Solve -2*p + 5*n - 1 = 0, -3*n + 2 = 3*p - 7*n for p.

2

Solve -2*w = -0*w + q - 12, 0 = -3*q + 12 for w.

4

Solve 0 = x - 5*l + 1, -5*x - 167 + 162 = 5*l for x.

-1

Solve 16*k - 13*k - 4*p = 27, -3*p - 34 = -5*k for k.

5

Solve -5*k - 16 = 3*t, 23*t - 5*k - 14 = 25*t for t.

-2

Solve 66*o - 2 = w + 65*o, 5*o - 13 = 2*w for w.

1

Solve -5*k + 5*f = -15, -5*f + f + 6 = 2*k for k.

3

Solve -4*b = -2*g + 12, -g + 4*b = 4*g for g.

-4

Solve 2*c = -y, 0 = -5*c + 3*y + 30 - 8 for c.

2

Solve 10 = -f - 2*l, l + 5 = -2*f + 7*f for f.

0